Industrial and organizational psychology : linking theory with practice - Cooper, Cary L.,; Locke, Edwin A., (Blackwell Business, 2000)
Incentives. Workplace interventions to prevent stress-related illness. Advances in leadership training and development. The pursuit of organizational justice...